Innovation in the maritime sector: aligning strategy with outcomes. Issue 8 (16th November 2020) - Acciaro, Michele; Sys, Christa
ABSTRACT: Innovation is identified as one of the main avenues to maintain competitiveness and its importance is well established in business studies. Along maritime logistics chains, innovation is being increasingly recognized as a determinant of success. However, beyond the naval architecture literature, little attention has been given to the role that innovation plays in maritime business. Notwithstanding the increasing number of innovation efforts that can be traced in the industry, little is known of the processes and mechanisms that make innovation successful, with the result that initiatives are often uncoordinated, unfocused, poorly managed, and do not deliver the expected results. In order to improve innovation processes, better insight is needed into what motivates innovation along maritime supply chains, in particular for ocean carriers, (inland) terminal operators, port managers, and hinterland transport operators. To this end, the paper proposes an index-based approach using data collected for 59 innovation cases to capture the degree of alignment between innovation strategy and outcomes in various maritime logistics business sectors. Substantial misalignment exists between company strategies and innovation success, and efforts should be made to improve the strategic processes that lead to collaborative innovation in maritime supply chains.